1999
DOI: 10.1525/aa.1999.101.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Color Appearance and the Emergence and Evolution of Basic Color Lexicons

Abstract: Various revisions of the Berlin and Kay (1969) model of the evolution of basic color term systems have been produced in the last thirty years, motivated by both empirical and theoretical considerations. On the empirical side, new facts about color naming systems have continually come to light, which have demanded adjustments in the descriptive model. On the theoretical side, there has been a sustained effort to find motivation in the vision science literature regarding color appearance for the synchronic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(201 citation statements)
references
References 79 publications
7
188
2
4
Order By: Relevance
“…All of the optimal configurations were obtained by starting from a random assignment of category labels to chips. In contrast, the color-naming system of a given language has a history: It has evolved not from a random state, but rather from an earlier category system, usually one with exactly one fewer categories (1,19). Thus, some languages may not approximate maxima in well-formedness as much as they do points on an evolutionary path leading from one maximum in wellformedness to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the optimal configurations were obtained by starting from a random assignment of category labels to chips. In contrast, the color-naming system of a given language has a history: It has evolved not from a random state, but rather from an earlier category system, usually one with exactly one fewer categories (1,19). Thus, some languages may not approximate maxima in well-formedness as much as they do points on an evolutionary path leading from one maximum in wellformedness to another.…”
Section: Discussionmentioning
confidence: 99%
“…We took as our empirical base the color-naming data of the World Color Survey (WCS) (18,19). These data were obtained by using a stimulus palette of 330 colors, as approximated in Fig.…”
Section: The World Color Surveymentioning
confidence: 99%
“…He reports that his "results largely confirm the generalizations that [Kay & Maffi (1999) and Kay et al (1991)] achieved with non-statistical techniques, even though not all the proposed universals could be confirmed" (p. 525). The biggest difference Jäger found between his PCA analysis and the non-statistical analysis of Kay & Maffi (1999) was that he found yellow more frequently associated with white than they did (p. 533). In a follow-up analysis to their 2006 paper, Lindsey and Brown (2009) found that although there is significant variation across speakers of the same language,…”
mentioning
confidence: 76%
“…Drawing on similarities to word processing Elliot and Maier (2012) (Kinsch & Mangalath, 2011), the meaning of a color is determined by its contextual surround. Some colors, especially those most salient across time, language, and culture (i.e., white, black, and red;see Berlin & Kay, 1969;Kay & Maffi, 1999;Kuehni, 2007) (Baumeister, Bratslavsky, Finkenauer, & Vohs, 2001 Meier, D'Agostino, Elliot, Maier, and Wilkowski (2012) introduced an experimental manipulation of the context in which the color red was perceived. Participants were told that they will be interviewed by another person in a separate room about "dating" (i.e., a romantic context) or about "your intelligence" (i.e., an achievement context) and were shown a color-primed picture of one of the several possible interviewers.…”
Section: The Influence Of Red As a Function Of The Psychological Contextmentioning
confidence: 99%